2018
DOI: 10.1002/adhm.201800080
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Neural Stem Cell Delivery System for Neurodegenerative Diseases Treatment

Abstract: Transplanted stem cells constitute a new therapeutic strategy for the treatment of neurological disorders. Emerging evidence indicates that a negative microenvironment, particularly one characterized by the acute inflammation/immune response caused by physical injuries or transplanted stem cells, severely impacts the survival of transplanted stem cells. In this study, to avoid the influence of the increased inflammation following physical injuries, an intelligent, double-layer, alginate hydrogel system is desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The percentage of transplanted survival cells is limited by acute inflammation after injury or transplantation. Therefore, an intelligent double-layer alginate hydrogel system was designed in which an inner layer modified with alginate MMP and RGD polypeptides to improve neural stem cells (NSCs) adhesion, and an outer layer contains Cripto-1 antibodies to facilitate differentiation of NSCs to dopaminergic neurons for treatment of Parkinson’s disease [ 98 ]. In summary, the few covered studies here revealed the feature of injectable self-healable hydrogels to modulate growth, survival, and differentiation of neural cells to target stem cell therapy for the degenerated CNS.…”
Section: Tissue Engineering Applications and Cancer Drug Deliverymentioning
confidence: 99%
“…The percentage of transplanted survival cells is limited by acute inflammation after injury or transplantation. Therefore, an intelligent double-layer alginate hydrogel system was designed in which an inner layer modified with alginate MMP and RGD polypeptides to improve neural stem cells (NSCs) adhesion, and an outer layer contains Cripto-1 antibodies to facilitate differentiation of NSCs to dopaminergic neurons for treatment of Parkinson’s disease [ 98 ]. In summary, the few covered studies here revealed the feature of injectable self-healable hydrogels to modulate growth, survival, and differentiation of neural cells to target stem cell therapy for the degenerated CNS.…”
Section: Tissue Engineering Applications and Cancer Drug Deliverymentioning
confidence: 99%
“…However, the xenogeneic nature of ECM‐based scaffolds and the potential immune response to the antigenic components of xenogeneic materials represent a critical barrier to the use of xenogeneic scaffolds in translational applications . Synthetic ECM‐derived peptides, such as laminin‐derived IKVAV and fibronectin‐derived RGD were used to form ECM‐mimetic hydrogels by self‐assembly or incorporation with other biopolymer materials (e.g., hyaluronic acid and alginate) to allow effective delivery and differentiation of stem cells to the brain, without the use of xenogeneic materials.…”
Section: Applications Of Advanced Biomaterials For Stem Cell Deliverymentioning
confidence: 99%
“…A double-layered alginate hydrogel system consisting of matrix-metalloproteinases and Arg-Gly-Asp (RGD) peptide in the inner layer was designed to allow transplanted stem cells to proliferate and mobilize to the outer layer following the inflammatory storm caused from surgery. 50 Following transplantation of neural stem cells (NSCs) into a rat brain trauma model, the double-layered alginate hydrogel promoted survival and differentiation of the NSCs. This overall approach focused on NSCs, which have a reduced risk of teratoma formation compared to human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs), but the design could be easily adapted to other types of transplanted cells.…”
Section: Cell Delivery In Encapsulating Hydrogelsmentioning
confidence: 99%
“…that downregulate gene expression as an effective alternative tool to drive osteogenesis. 50 In addition, the hydrogel's tunable design provides controllable swelling and degradation properties that can be used for prolonged delivery of gene therapies in order to extend the regulation of the transplanted cell behavior.…”
Section: Reviewmentioning
confidence: 99%